2007
DOI: 10.1017/s0954422407782884
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of oats as it relates to cardiovascular disease

Abstract: The food consumption of oats has increased in recent years due to a perceived association with a range of health benefits. Oats are unusual in that the bran is not as physically distinct as in other cereals. This provides a possible benefit in providing a high β-glucan content of the grains. However, oats contain many other phytochemicals including a range of antioxidants that may be associated with health benefits, although the evidence for such benefits is largely indirect and often confusing and contradicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 166 publications
(275 reference statements)
0
59
0
Order By: Relevance
“…but the obtained a-tocopherol results were similar to results described in the literature. In Australia using a similar analytical method the range of a-tocopherol concentration was 7.0 to 14.9 mg kg -1 for husked oats (Ryan et al, 2007) while in Poland and Great Britain the concentration of a-tocopherol in this type of oat was from 8.5-8.9 mg kg -1 (Zielinski et al, 2001;White et al, 2006). This suggests that in warmer climates, as in Australia, the a-tocopherol concentration is higher than in countries with a cooler climate -Poland, Great Britain and Latvia.…”
Section: Discussionmentioning
confidence: 99%
“…but the obtained a-tocopherol results were similar to results described in the literature. In Australia using a similar analytical method the range of a-tocopherol concentration was 7.0 to 14.9 mg kg -1 for husked oats (Ryan et al, 2007) while in Poland and Great Britain the concentration of a-tocopherol in this type of oat was from 8.5-8.9 mg kg -1 (Zielinski et al, 2001;White et al, 2006). This suggests that in warmer climates, as in Australia, the a-tocopherol concentration is higher than in countries with a cooler climate -Poland, Great Britain and Latvia.…”
Section: Discussionmentioning
confidence: 99%
“…Cereals account for phenolic compounds derived mainly from hydroxybenzoic and hydroxycinnamic acids. Early studies have shown that the phenolic acids in oat possess antioxidant properties both in vitro (Peterson 2001;Shewry et al 2008) and in vivo (Ryan et al 2007). The major phenolic acids in oats are ferulic, p-coumaric, caffeic, vanillic, hydroxybenzoic acid and their derivatives (Matilla et al 2005;Kova cova and Malinova 2007).…”
Section: Nutritional Components Of Oatsmentioning
confidence: 99%
“…Thus, the crimped oats contained within the test meal did not make a major contribution to the plasma flavonol concentration found in horses. Total flavonoids in oats, including quercetin, were reported to be 0.177 mg/g [25]. The mean supplemented quercetin dose as a part of the test meal was approximately 6,300 mg/horse.…”
Section: Discussionmentioning
confidence: 99%